2020
DOI: 10.2217/cer-2020-0058
|View full text |Cite
|
Sign up to set email alerts
|

Type I collagen matrix plus polyhexamethylene biguanide antimicrobial for the treatment of cutaneous wounds

Abstract: Aim: Determine the effectiveness of purified native type I collagen matrix plus polyhexamethylene biguanide antimicrobial (PCMP) on cutaneous wounds. Materials & methods: A prospective cohort study of 307 patients (67 venous leg ulcers, 62 diabetic foot ulcers, 45 pressure ulcers, 54 postsurgical wounds and 79 other wounds) was conducted. Results: Cox wound closure for PCMP was 73% at week 32. The median time to wound closure was 17 weeks (Kaplan–Meier). The incidence of PCMP-treated wounds showing >60%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Other studies in porcine models and in humans have demonstrated that another form of debridement, enzymatic debridement, may decrease wound size, reduce inflammation, and increase granulation tissue, with the caveat that they may require a secondary dressing to penetrate the rooted layers of the wound in order to control the biofilms present [ 139 , 140 , 141 ]. Likewise, it has been shown that hydro-active dressing soaked with polyhexamethylene biguanide (in humans) can promote macrophage activation in the wound, inhibiting bacterial proliferation and dampening inflammation [ 138 , 142 , 143 ].…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…Other studies in porcine models and in humans have demonstrated that another form of debridement, enzymatic debridement, may decrease wound size, reduce inflammation, and increase granulation tissue, with the caveat that they may require a secondary dressing to penetrate the rooted layers of the wound in order to control the biofilms present [ 139 , 140 , 141 ]. Likewise, it has been shown that hydro-active dressing soaked with polyhexamethylene biguanide (in humans) can promote macrophage activation in the wound, inhibiting bacterial proliferation and dampening inflammation [ 138 , 142 , 143 ].…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…To build on the current evidence base and further elucidate how processing methodologies (e.g., layering and crosslinking) impact key properties, we utilized commercially available products constructed of SIS and OFM and evaluated matrix structure and protease attenuation; this analysis was complimented by the development and application of an in vitro degradation chronic wound model to study scafold degradation dynamics and functionality [4,[29][30][31]. Here, both SIS and OFM were able to attenuate MMPs; however, structural and functional properties determined the magnitude of MMP reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Te products in this study are both native collagen ECMs, with SIS undergoing layering and an additional chemical crosslinking process. Both tissue sources have been shown clinically to support progression through the wound healing phases [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…It is a novel product enabling a proactive BBWM approach that constitutes 2 crucial elements: i) physical removal of the biofilm via debridement and ii) restricting the biofilm reformation via a broad spectrum, nontoxic, and positively charged antimicrobial agent polyhexamethylene biguanide. [ 167,168 ] The EDC (1‐ethyl‐3‐(3‐dimethylamino propyl) carbodiimide) chemically cross‐linked native ECM strengthens the matrix bonds to enhance resistance against MMPs. The combination of both native crosslinked ECM and broad‐spectrum polyhexamethylene biguanide prevents a proinflammatory hyper proteolytic environment that stalls the healing of wounds.…”
Section: Commercial Products For Chronic Wounds Treatmentmentioning
confidence: 99%